Dosificación de Hormigones con áridos reciclados mezclados con y sin finos. Residuos de planta de la Habana - Outeriño Nuñez, Maidiel (Universidad Central "Marta Abreu" de las Villas, 2014)
Presently investigation work, evaluates the use of arid recycled and fine recycled in the production of structural concretes. Once selected the raw mix in the plant in Alamar, made the characterizations in the Technical Center for the Development of the Materials of Construction (C.T.D.M.C.), of the necessary materials to produce hydraulic concretes. It decided that the substitution percent of coarse natural, will by 25% and 100%, fine natural sand was substituted 50%, and add of filler 3% and 6 smaller% that the sieve 200. In the stage of production of concretes, the properties were evaluated in fresh state, as the establishment and their density. In the age of break of 7 and 28 days, they were not carried out rehearsals destructive and destructive. Inside those no destructive sclerometer and ultrasound, and inside of the destructive resistance to compression. Inside the conclusions that you arrived, it stands out that the use of arid recycled and fine recycled, it facilitates the obtaining of acceptable results in the production of structural concretes.
Keywords: Hormigones con Áridos Reciclados; Residuos de Planta de la Habana; Hormigones Estructurales; Centro Técnico para el Desarrollo de los Materiales de Construcción